Automated Synthesis of 18F-BCPP-EF {2-tert-Butyl-4-Chloro-5-{6-[2-(2[18F]fluoroethoxy)-Ethoxy]-Pyridin-3-ylmethoxy}-2H-Pyridazin-3-One for Imaging of Mitochondrial Complex 1 in Parkinson’s Disease - Kaur, Tanpreet; Brooks, Allen F.; Liddell, Katherine M.; Henderson, Bradford D.; Hockley, Brian G.; Bohnen, Nicolaas I.; Albin, Roger L.; Scott, Peter J. H. (Frontiers in Chemistry, 2022)
Mitochondrial complex I (MC-I) is an essential component of brain bioenergetics and can be quantified and studied using positron emission tomography (PET). A specific high affinity 18F radiotracer for MC-I enables monitoring of neurodegenerative disease progression and pathology via PET imaging. To facilitate clinical research studies tracking MC-I activity in Parkinson’s disease and other neurodegenerative diseases, a fully automated synthesis of the recently described 2-tert-butyl-4-chloro-5-{6-[2-(2[18F]fluoroethoxy)-ethoxy]-pyridin-3-ylmethoxy}-2H-pyridazin-3-one ([18F] BCPP-EF, [18F]1) was developed. We report the first automated synthesis [18F]BCPP-EF using a green radiochemistry approach. The radiotracer was synthesized with good radiochemical yield, excellent radiochemical purity, and high molar activity.